Aid for Trade, Infrastructure, and the Growth Effects of Trade Reform : Issues and Implications for Caribbean Countries - Moreira, Emmanuel Pinto (2012)
This paper examines how aid-for-trade programs can help to magnify the growth benefits that developing countries can reap from trade reform and global integration, with a special emphasis on the Caribbean region. The first part discusses various rationales for trade-related aid, viewed both as a compensatory scheme (aimed at cushioning the impact of revenue cuts and adjustment costs) and a promotion scheme (aimed at alleviating supply-side constraints). In the latter case, particular attention is paid to the role of infrastructure as a constraining factor on trade expansion. The second part discusses the relevance of aid-for-trade arguments for Caribbean countries and identifies a number of specific issues for the region. The third part illustrates the potential growth effects of aid-for-trade programs with simulation results for the Dominican Republic -- a country where infrastructure indicators remain relatively weak. The results illustrate the potentially large growth benefits that a temporary and well-targeted aid-for-trade program can provide to countries of the region.